Environmental influences on baterial diversity of soils on signy island, maritime antarctic - Chong, C.W.; Dunn, M.J.; Convey, P.; Tan, G.Y.A.; Wong, R.C.S.; Tan, I.K.P. (2009)
Soil bacterial diversity at environmentally distinct locations on Signy Island, South Orkney Islands was examined using the denaturing gradient gel profiling approach. A range of chemical variables in soils at each site was determined in order to describe variation between locations. No apparent differences in Shannon Diversity Index (H') were observed. However, as revealed in an analysis of similarity (ANOSIM), the dominant bacterial communities of all eight studied locations were significantly different. Within this, higher levels of similarity were observed between penguin rookeries, seal wallows and vegetated soils, all of which share varying levels of impact from vertebrate activity, in contrast with more barren soil. In addition, the lowest H' value was detected from the latter soil which also has the most extreme environmental conditions, and its bacterial community has the greatest genetic distance from the other locations. DGGE analyses indicated that the majority of the excised and sequenced bands were attributable to the Bacteroidetes. Across a range of ten environmental variables, multivariate correlation analysis suggested that a combination of pH, conductivity, copper and lead content potentially contributed explanatory value to the measured soil bacterial diversity.